Viral subversion of host cell Ca²⁺ signaling through STIM1-Orai1-mediated SOCE: Mechanisms and implications - Qingqing Lu; Yuan Ding; Yan Zhang; Shuzhen Liu (Pharmacological Research)
Viral infection hijacks host cell physiological processes to replicate and spread, in which the calcium ion (Ca2 +) signaling pathway plays a key role in the viral life cycle. Store-operated Ca2+ entry (SOCE), as the major Ca²⁺ influx pathway, is regulated by the endoplasmic reticulum (ER) Ca2+ receptor stromal interaction molecules 1 (STIM1) and plasma membrane channel protein Orai1. Recent studies have shown that viruses disrupt intracellular Ca2+ homeostasis by regulating the STIM1-Orai1-mediated SOCE pathway, thereby promoting viral entry, replication, and pathogenicity. This review systematically summarizes the mechanism of STIM1/Orai1 in viral infection and reveals the molecular basis of the Ca2+ signaling pathway hijacked by viruses, offering a new perspective for understanding the pathogenicity of viruses. To further advance this understanding, future studies should focus on the interaction between viral proteins and STIM1-Orai1 and its downstream signaling network, and aim to develop highly selective inhibitors targeting the SOCE pathway to provide new strategies for antiviral therapy and drug research and development. Collectively, these studies not only deepen the understanding of virus-host interactions but also lay the theoretical foundation for precision medicine and antiviral therapy.